Developing HOT-LAB-Based Physics Practicum E-Module to improve Practicing critical thinking skills - Riki Putra Purnama; Rena Agustina Denya; Pina Pitriana; Shidiq Andhika; Moh Diki Dermawan Setia; Elsya Nurfadillah (Journal of Science Education Research, 2021)
Practicum activity is a scientific process to find out a phenomenon or validate a concept. HOT-LAB in laboratory activities is useful in improving 4C skills, including Critical Thinking Skills. The number of Modules or E-Modules that use a cookbook of guided laboratory inquiries was less to increase the 4C Skills in supporting the 21st Century skills. This study aimed to design, create and find out the effect of using HOT-LAB-based E-Modules to improve the students’ Critical Thinking Skills. The research method was the ADDIE RnD. Invalidation stage, E-Module that was validated by material and media validators, stated effective, so it was feasible to continue to data collection of students. Data of Critical Thinking Skills used 30 students as subjects whose raw data was analyzed using statistical tests. E-Module obtained a validity score of 83.33% on the material validation and 84.6% on the media validation. Moreover, the statistical test showed that there is a significant change in implementing E-Module, which means that the HOT-LAB-based E-Module improved the students' Critical Thinking Skills.